Strategies for enrichment and purification of polyphenols from fruit-based materials. (January 2019) - Kelly, N.P.; Kelly, A.L.; O'Mahony, J.A.
Abstract: Background: Polyphenols are important components of plants, and contribute to colour, aroma and taste, as well as having many other functions. In recent years, considerable research has been conducted on polyphenols in foods, focusing on their bioavailability, metabolism and biological effects. This was driven by results of epidemiological studies which showed that diets rich in plant foods are associated with decreased incidence of cancer and heart diseases. Fruits are rich in polyphenols, and the extraction and enrichment of these bioactive compounds from fruit is of increasing academic and commercial interest. Scope and approach: In this review, the numerous approaches that have been investigated and utilised for the enrichment of polyphenols in foods over the last 20 years or so are discussed, mainly focusing on fruit-based products. This review summarises some important aspects of traditional polyphenol enrichment processes such as solvent extraction, as well as reviewing some novel approaches such as the use of colloidal gas aphrons and ohmic heating. Applications of each process are explained, advantages and disadvantages discussed, and recovery and enrichment levels of polyphenols presented. Key findings and conclusions: Pre-treatments such as enzymatic hydrolysis, pulsed electric fields and high-pressure processing can be applied to fruit-based products to improve polyphenol extraction efficiency. There is high potential for the use of environmentally friendly processes for enrichment of polyphenols from fruit-based products using membrane filtration. Polyphenol enrichment technologies need to be cost-effective and rapid and facilitate retention of the biological activities of the polyphenols. Highlights: Recovery of polyphenols is widely researched due to their potential applications. The food industry requires clean and cost-effective polyphenol enrichment processes. Membrane technology and pressurised liquid extraction are potentially exciting. Solvent extraction has poor selectivity and generates solvent waste streams. Pre-treatments, e.g., ohmic heating, can be used to improve extraction efficiency.